Constrained model predictive control for Markov jump system with disturbances - Zhang, Y.; Yin, YanYan; Liu, F. (2015)
© 2015 Technical Committee on Control Theory, Chinese Association of Automation.This study is concerned with model predictive control (MPC) for a class of discrete-time Markov jump system with disturbances. A synthesis method to design robust model predictive controller is proposed by considering H2/H8 performance index, a serious of sufficient conditions are obtained which guaranteeing the stability of system, meanwhile satisfying the constraints. Finally, a numerical example is presented to illustrate the effectiveness of the developed results.